From Organisational Awareness to Integration: Embedding DEI into Strategic HRM in a Multinational Context : Case Kalmar Finland Oyj - Petroff, Jasmin (My University, 2025)
Global organisations are increasingly expected to create diverse, equitable, and inclusive workplaces. However, many DEI initiatives remain isolated, limiting their long-term effectiveness. This master's thesis examines how DEI principles can be moved from standalone initiatives to become an integrated part of Strategic Human Resource Management (SHRM) and core HR practices. The theoretical foundation of the thesis is built on three key theoretical concepts: Strategic Human Resource Management (SHRM), Core HR Practices, and Diversity, Equity, and Inclusion (DEI). These concepts are explored to explain how DEI is embedded into HR strategy and reinforced through the core HR practices of recruitment, resourcing, learning and development, performance management, and compensation and recognition. This theoretical overview clarifies the rationale for positioning DEI as a strategic imperative, demonstrating its potential to strengthen organisational value. The empirical part of the research was conducted as a qualitative holistic single-case study in collaboration with Kalmar Oyj, a global heavy machinery company operating in a traditionally male-dominated industry. The primary data was collected through semi-structured interviews with HR professionals and business managers. The data was analysed using thematic analysis to identify the current state of DEI integration, key enablers and barriers impacting the process as well as the perceived impact of DEI integration. The results indicate that the case organisation is currently in a transitional phase, defined by a "push and pull" dynamic. Progress is enabled by strong executive sponsorship, data transparency and targeted inclusive leadership training, which are driving awareness and practical implications. However, significant barriers remain. The study identifies a structural scarcity of diverse talent in the industry, often compounded by a conflict between operational speed and diversity goals; managers frequently feel pressured to prioritise filling vacancies quickly over building diverse candidate pools. Additionally, the lack of a unified company-wide DEI strategy has led to inconsistent practices across divisions. Furthermore, the analysis demonstrates that the "People Case" for DEI, especially for the creation of psychological safety and belonging is not simply an ethical preference but the essential prerequisite for unlocking the "Business Case" of innovation and performance.
Keywords: human resource management; diversity; inclusion; organisaatiokulttuuri; strateginen johtaminen; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master's Degree Programme in International Business; Henkilöstöjohtaminen